How Innovation Districts (Do Not) Work: the Case Study of Cracow - Gądecki, Jacek; Afeltowicz, Łukasz; Anielska, Karolina; Morawska, Ilona (European Spatial Research and Policy, 2020)
This article is an attempt to answer the question: how one selects a neighbourhood to develop an innovation district, using the case of Cracow. This article mainly refers to the issue of the shape of innovation districts, showing how much the morphology of such spaces and their functions can promote or limit the development of innovative enterprises from the Information and Communication Technologies (ICT) industry. It also refers to our research carried out with quantitative and qualitative methods in Poland, using two locations in Cracow as a case study. In this paper, we focus on the significant restrictions which hinder the emergence and development of such districts. We also indicate the potential solutions to these difficulties such as the temporary spaces of events we mapped and which we called ‘totemic spaces’.